Composite Membrane Formation by Combination of Reaction‐Induced and Nonsolvent‐Induced Phase Separation - Aburabie, Jamaliah; Villalobos, Luis Francisco; Peinemann, Klaus‐Viktor (Macromolecular materials and engineering, 2017)
A novel method of preparing skinned asymmetric membranes with two distinctive layers is described: a top layer composed of chemically cross‐linked polymer chains (dense layer) and a bottom layer of non‐cross‐linked polymer chains (porous substructure). The method consists of two simple steps that are compatible with industrial membrane fabrication facilities. Unlike conventional processes to prepare asymmetric membranes, with this approach it is possible to finely control the structure and functionalities of the final membrane. The thickness of the dense layer can be easily controlled over several orders of magnitude and targeted functional groups can be readily incorporated in it. Novel method of preparing skinned asymmetric membranes with two distinctive layers is described: a top layer composed of chemically cross‐linked polymer chains (dense layer) and a bottom layer of non‐cross‐linked polymer chains (porous substructure). With this approach it is possible to tune the structure and functionalities of the final membrane as well as control the thickness of the dense layer.